Statistical tables - Rohlf, F. James; Sokal, Robert R. (San Francisco : W. H. Freeman, 1969)
Each table is accompanied by ... a reference to the section or sections in our textbook Biometry giving explanations and applications of the table.
Prepared in conjunction with the textbook by R. R. Sokal and F. J. Rohlf: Biometry; the principles and practice of statistics in biological research.
lje 23/01/2019
Loans
Keywords: Biometry; Mathematical statistics; Statistics